Analisis Perbandingan atas ROA Sebelum dan Setelah Penerbitan Laporan Keberlanjutan - Wijaya, Aida; Novianto, Robertus Ary (Jurnal Ilmiah Wahana Akuntansi, 2023)
Sustainability Development Goals had become a mandatory activity for public company in Indonesia. It is according to the regulation from the Financial Service Audthority – FSA No.51/OJK.03/2017. The regulation requires that public companies follow the items to be done and then report it in the Sustainability Report. Along with the integration of the sustainability activity into the operational activity of companies, it is assumed that there would be a change toward better company performance. Using the paired sample t-test, this research analyzed the difference of company’s performance before and after the issuance of its Sustainability Report. Using Return On Assets as the proxy of the perfomance, the research found that there was no significant difference of it before and after the issuance of Sustainability Report